2009
DOI: 10.17660/actahortic.2009.808.36
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas Species Causing Bacterial Spot of Tomato in the Russian Federation

Abstract: Bacterial spot of tomato, caused by Xanthomonas euvesicatoria (Group A), X. vesicatoria (Group B), X. perforans (group C) and X. gardneri (Group D) (Jones et al., 2004), formerly known as X. campestris pv. vesicatoria, has become very important in the Russian Federation. Leaf spots and wilt symptoms were observed in 2006 in tomato fields located in southern European part of Russia. Field symptoms were first observed in early July of 2006 and had spread to over 30% of the plants in some fields by late August. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Although no marked intraspecific variation was detected in Xp, Xv, and Xg, a recombinant lineage of Xeu was detected. In Russia, both Xg and Xv strains were recovered from infected tomatoes in 2006 (65). Interestingly, this study also identified strains from 1947-1949 as Xv and Xg, indicating the presence of Xg earlier than its first description in Yugoslavia in 1957.…”
Section: Shift In Species Distribution and Prevalence On Tomatomentioning
confidence: 63%
“…Although no marked intraspecific variation was detected in Xp, Xv, and Xg, a recombinant lineage of Xeu was detected. In Russia, both Xg and Xv strains were recovered from infected tomatoes in 2006 (65). Interestingly, this study also identified strains from 1947-1949 as Xv and Xg, indicating the presence of Xg earlier than its first description in Yugoslavia in 1957.…”
Section: Shift In Species Distribution and Prevalence On Tomatomentioning
confidence: 63%
“…X. perforans is reported to be present in the USA, Mexico, Brazil, Thailand (Jones et al, 2004), some islands of the Indian Ocean (Hamza et al, 2010) and Tanzania (Mbega et al, 2012). X. gardneri was isolated in the USA (Kim et al, 2010;Ma et al, 2011), Costa Rica ), Canada, Brazil (Quezado-Duval et al, 2005, Russia (Kornev et al, 2009) and some islands of the Indian Ocean (Hamza et al, 2010).…”
Section: Global Distributionmentioning
confidence: 99%
“…The pest identity according to the new classification is, in most cases, -not stated/updated‖, since most of the reports date from before the new classification. According to the EPPO PQR database (EPPO, online), X. vesicatoria is widely distributed in all five continents (Ignatov et al, 2009;Kornev et al, 2009, Mbega et al, 2012. X. euvesicatoria is present in the USA (Ma et al, 2011), Tanzania (Mbega et al, 2012), some islands of the Indian Ocean (Hamza et al, 2010) and Serbia (Ignjatov et al, 2010;Gasić et al, 2011).…”
Section: Global Distributionmentioning
confidence: 99%
“…Surveys on the occurrence of this bacterial complex in tomato have been made in different localities of Brazil and around the world (Quezado-Duval et al 2005;Kornev et al 2009;Myung et al 2009;Hamza et al 2010;Pereira et al 2011). However, there are still few reports concerning the role of weeds in the epidemiology of tomato bacterial spot.…”
Section: Introductionmentioning
confidence: 99%